Association between dipeptidyl peptidase-4 inhibitor drugs and risk of acute pancreatitis: A meta-analysis. Issue 48 (December 2017) - Chen, Shimin; Zhao, Enfa; Li, Wenfei; Wang, Jiehong
Abstract: Background: Previous studies have reported conflicting results for the relationship between dipeptidyl peptidase-4 (DPP-4) inhibitor drugs and acute pancreatitis. The aim of this study was to investigate the association between DPP-4 inhibitors and an increased risk of acute pancreatitis using meta-analysis. Methods: We conducted a comprehensive search in PubMed, Embase, Web of Science, and Cochrane library from inception to March 4, 2017. Original articles with data on DPP-4 inhibitors and acute pancreatitis were included. We used random-effects models or fixed-effects models to combine the relative risks (RRs), odds ratio (OR), and hazard ratio (HRs) with 95% confidence intervals (CIs) in randomized controlled studies, case–control study and cohort study, respectively. Results: Five case–control studies, 5 randomized controlled studies, and 3 cohort studies were selected of the 451 retrieved abstracts. A higher risk of acute pancreatitis was observed with the following RR/OR and 95%CI: RR 1.67 (1.08–2.59) in randomized controlled studies and OR 1.45 (1.30–1.61) in case–control studies. However, the pooled HR of the 3 cohort studies failed to confirm this association. Conclusion: There is a marginally higher risk of acute pancreatitis with DPP-4 inhibitors. However, this risk was not observed in cohort studies. Thus, further clinical trials are required to confirm this finding.